Titanium metal surface high-hardness carbonized layer and preparation method thereof

By generating a high-hardness carbide layer in situ on the surface of the titanium alloy, the problem of insufficient wear resistance of titanium alloy is solved, and the effect of improving the wear resistance of titanium alloy is achieved, and this method is suitable for mass production.

CN119736622AActive Publication Date: 2025-04-01XIAN UNIV OF TECH

Patent Information

Application Number
CN202411922741.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The poor wear resistance of titanium alloys limits its further expansion in applications in multiple fields.

Method used

By selecting high-purity graphite as the carbon diffusion source, using electric field to assist carbon atom diffusion, a high-hardness carbonized layer is generated on the surface of the titanium alloy in situ. Specific steps include cleaning, drying, forming a diffusion couple, electric field diffusion and low-temperature annealing treatment.

Benefits of technology

It effectively improves the wear resistance of titanium alloy, and the formed carbonized layer has high binding force and stability, short preparation time and high production efficiency, which is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736622A_ABST
    Figure CN119736622A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-hardness carbonized layer on a titanium metal surface, which comprises the following steps: step 1, selecting high-purity graphite as a carbon diffusion source, and selecting a high-strength titanium alloy as a matrix titanium alloy; 2, the high-strength titanium alloy is placed in a vacuum box to be dried after being cleaned, and a graphite block is tightly pressed on the surface of the high-strength titanium alloy to form a diffusion couple; 3, the upper end and the lower end of the diffusion couple are connected with a positive electrode and a negative electrode correspondingly, the diffusion couple is put into a vacuum box, interface atoms of the high-strength titanium alloy and graphite are mutually diffused under the action of an electric field, and a TiC wear-resisting layer is prepared on the surface of the high-strength titanium alloy; 4, the high-strength titanium alloy with the TiC wear-resistant layer on the surface is put into a vacuum heat treatment furnace to be subjected to low-temperature annealing treatment, and a high-hardness carbonized layer is prepared on the surface of the high-strength titanium alloy; the carbonization layer can improve the surface hardness of the titanium alloy and improve the strength and wear resistance of the titanium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium alloy surface hardening treatment, and specifically relates to a high-hardness carbide layer on the surface of titanium metal and a preparation method thereof. Background Art

[0002] Compared with other metals, titanium alloy plays an important role in aerospace, medical, industrial, military and construction fields due to its unique advantages of low density and high strength ratio. However, the disadvantage of poor wear resistance of titanium alloy limits its further expansion of application areas. Low wear resistance may cause titanium alloy parts to be damaged quickly and shorten their service life.

[0003] Titanium carbide has good thermal conductivity, wear resistance and low wear rate. Its grinding ability is comparable to that of artificial diamond and its cost is low, making it one of the ideal choices for manufacturing wear-resistant materials. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a high-hardness carbide layer on the surface of titanium metal. The prepared carbide layer can improve the wear resistance of the titanium alloy.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a high-hardness carbide layer on the surface of titanium metal, characterized in that it specifically comprises the following steps:

[0007] Step 1, selecting high-purity graphite with high electrical conductivity and high thermal conductivity as a carbon diffusion source, and selecting a high-strength titanium alloy as the matrix titanium alloy;

[0008] Step 2, placing the high-strength titanium alloy in an ultrasonic cleaning instrument, removing oil, wax and other organic substances on the surface of the high-strength titanium alloy by cleaning with an alkaline cleaning agent, then placing the high-strength titanium alloy in a vacuum box for drying, and finally pressing a graphite block tightly on the surface of the high-strength titanium alloy to form a diffusion couple, wherein the upper end of the diffusion couple is the graphite block and the lower end is the high-strength titanium alloy, wherein the entire outer surface of the high-strength titanium alloy is pressed with the graphite block;

[0009] Step 3, the upper and lower ends of the diffusion couple formed in step 2 are connected to positive and negative electrodes respectively, and placed in a vacuum box, and the interface atoms of the high-strength titanium alloy and graphite diffuse with each other under the action of the electric field, so that a TiC wear-resistant layer is prepared on the surface of the high-strength titanium alloy;

[0010] Step 4, placing the high-strength titanium alloy with a TiC wear-resistant layer on the surface prepared in step 3 into a vacuum heat treatment furnace for low-temperature annealing treatment, and finally preparing a high-hardness carbide layer on the surface of the high-strength titanium alloy.

[0011] Furthermore, in step 1, the carbon content of graphite is greater than 99.99%, and the high-strength titanium alloy composition is 55% Ti and 45% Nb.

[0012] Furthermore, in step 2, the high-strength titanium alloy is cleaned in an ultrasonic cleaning instrument for 5-10 minutes.

[0013] Furthermore, in step 2, the high-strength titanium alloy is placed in a vacuum oven and dried at a temperature of 160°C.

[0014] Furthermore, in step 2, the pressure used to tightly press the graphite block against the surface of the high-strength titanium alloy is 50-100 MPa.

[0015] Furthermore, in step 3, the vacuum degree of the vacuum box is 10 -2 -10 -3 , electric field conditions: current density 10-100A / cm 2 , current frequency 30-50Hz, pulse width 50-100μs, processing time 20s-5min, cool to room temperature after power-on, and inject high-purity argon into the vacuum box during cooling.

[0016] Furthermore, in step 4, the low-temperature annealing temperature is 550° C., and the low-temperature annealing time is 1.5 h.

[0017] According to the above-mentioned method for preparing a high-hardness carbide layer on the surface of titanium metal, a high-hardness carbide layer is prepared on the surface of titanium metal.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention generates high-strength titanium carbide in situ on the surface of titanium metal, with a short preparation time, and can effectively improve the wear resistance of titanium alloy;

[0020] The high-hardness carburized layer prepared by the present invention can form a titanium-carbon compound with strong bonding force and high stability;

[0021] The present invention adopts electric field to assist carbon atom diffusion, thus improving the rate of carbonized layer formation, and forming the carbonized layer uniformly, with high production efficiency, simple equipment operation, and batch production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a microstructure diagram of the interface between the high-hardness carbide layer prepared on the titanium metal surface and the titanium metal substrate in Example 1 of the present invention;

[0023] Figure 2 This is a microstructure diagram of the high-hardness carbide layer prepared on the titanium metal surface in Example 4 of the present invention. DETAILED DESCRIPTION

[0024] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0025] A method for preparing a high-hardness carburized layer on the surface of titanium metal, specifically comprising the following steps:

[0026] Step 1, select high-purity graphite with high electrical conductivity and high thermal conductivity as a carbon diffusion source, the matrix titanium alloy is selected from high-strength titanium alloy, the carbon content of graphite is greater than 99.99%, and the high-strength titanium alloy composition is 55% Ti content and 45% Nb content;

[0027] Step 2, placing the high-strength titanium alloy in an ultrasonic cleaning instrument, removing oil, wax and other organic substances on the surface of the high-strength titanium alloy by cleaning with an alkaline cleaning agent, cleaning the high-strength titanium alloy in the ultrasonic cleaning instrument for 5-10 minutes, and then placing the high-strength titanium alloy in a vacuum box for drying at a drying temperature of 160° C. Finally, pressing a graphite block tightly against the surface of the high-strength titanium alloy to form a diffusion couple, wherein the upper end of the diffusion couple is a graphite block and the lower end is a high-strength titanium alloy, wherein the entire outer surface of the high-strength titanium alloy is pressed with a graphite block, and the pressure used to press the graphite block tightly against the surface of the high-strength titanium alloy is 50-100 MPa;

[0028] Step 3: Connect the positive and negative electrodes at the upper and lower ends of the diffusion couple formed in step 2, and place them in a vacuum box with a vacuum degree of 10 -2 -10 -3 Under the action of electric field, the interface atoms of high-strength titanium alloy and graphite diffuse with each other. The electric field condition is: current density 10-100A / cm 2 , the current frequency is 30-50Hz, the pulse width is 50-100μs, the processing time is 20s-5min, and the power is turned on and cooled to room temperature. During the cooling process, high-purity argon gas is injected into the vacuum box to prepare a TiC wear-resistant layer on the surface of the high-strength titanium alloy;

[0029] Step 4, placing the high-strength titanium alloy with a TiC wear-resistant layer on the surface prepared in step 3 into a vacuum heat treatment furnace for low-temperature annealing treatment, the low-temperature annealing temperature is 550°C, the low-temperature annealing time is 1.5 hours, and finally a high-hardness carbide layer is prepared on the surface of the high-strength titanium alloy.

[0030] Example 1

[0031] Step 1: Select high-purity graphite with high electrical conductivity and high thermal conductivity as the carbon diffusion source, and the matrix titanium alloy is a high-strength titanium alloy. The carbon content of graphite is 99.995%, and the composition of the high-strength titanium alloy is 55% Ti and 45% Nb.

[0032] Step 2: Use alkaline cleaning agent to remove oil, wax and other organic substances from the surface of high-strength titanium alloy, clean it in an ultrasonic cleaning instrument for 5 minutes, dry it in a vacuum box, and then press the graphite block tightly on the surface of the titanium alloy to form a diffusion couple. The pressure used is 50MPa.

[0033] Step 3: Connect the positive and negative electrodes at the upper and lower ends of the above diffusion couple and place them in a vacuum box. Under the action of the electric field, the interface atoms of titanium and graphite diffuse with each other. The current density is 10A / cm 2 , a TiC wear-resistant layer is prepared. The vacuum degree is 10 -2 , current frequency 50 Hz, pulse width 50 μs, processing time 50 s, and high-purity argon gas was injected during cooling.

[0034] Step 4: Place the titanium metal with a high-hardness carbide layer in a vacuum heat treatment furnace for low-temperature annealing. The low-temperature annealing temperature is 550°C and the holding time is 1.5 hours. This makes the carbide layer structure on the alloy surface more stable while maintaining the toughness and ductility of the core material. Finally, a high-hardness carbide layer is prepared on the surface of the high-strength titanium alloy.

[0035] Figure 1 The interface microstructure diagram of the high hardness carbide layer on the titanium metal surface and the titanium alloy substrate prepared in Example 1 is shown in FIG. Figure 1 It can be seen that the diffusion interface is clear, without macroscopic defects such as cracking and shedding. According to the measurement, the depth of the carburized layer reaches 58um, and the average microhardness of the titanium alloy surface is 947.5HV 0.02 The friction coefficient is 0.231 and the volume wear rate is 5.12 x 10 - 6 mm 3 / Nm, with good wear resistance.

[0036] Example 2

[0037] Step 1: Select high-purity graphite with high electrical conductivity and high thermal conductivity as the carbon diffusion source, and the matrix titanium alloy is a high-strength titanium alloy. The carbon content of graphite is 99.995%, and the high-strength titanium alloy composition is 55% Ti and 45% Nb.

[0038] Step 2: Use alkaline cleaning agent to remove oil, wax and other organic substances from the surface of high-strength titanium alloy, clean it in an ultrasonic cleaning instrument for 8 minutes, dry it in a vacuum box, and then press the graphite block tightly on the surface of the titanium alloy to form a diffusion couple. The pressure used is 80MPa.

[0039] Step 3: Connect the positive and negative electrodes at the upper and lower ends of the above diffusion couple and place them in a vacuum box. Under the action of the electric field, the interface atoms of titanium and graphite diffuse with each other. The current density is 10A / cm 2 , TiC wear-resistant layer was prepared, and the vacuum degree was 10-3 , current frequency 30 Hz, pulse width 100 μs, processing time 1 min, and high-purity argon gas was injected during cooling.

[0040] Step 4: Put the titanium metal with high hardness carbide layer into a vacuum heat treatment furnace for low temperature annealing to make the structure of the carbide layer on the surface of the alloy more stable while maintaining the toughness and ductility of the core material. The low temperature annealing temperature is 550℃ and the holding time is 1.5h.

[0041] The high-hardness carburized layer on the titanium metal surface prepared in Example 2 has a carburized layer depth of 68 μm and an average microhardness of 960.21 HV 0.02 The friction coefficient is 0.225 and the volume wear rate is 4.36ⅹ10 -6 mm 3 / Nm, with good wear resistance.

[0042] Example 3

[0043] Step 1: Select high-purity graphite with high electrical conductivity and high thermal conductivity as the carbon diffusion source, and the matrix titanium alloy is a high-strength titanium alloy. The carbon content of graphite is 99.995%, and the composition of the high-strength titanium alloy is 55% Ti and 45% Nb.

[0044] Step 2: Use alkaline cleaning agent to remove oil, wax and other organic substances from the surface of high-strength titanium alloy, clean it in an ultrasonic cleaning instrument for 10 minutes, dry it in a vacuum box, and then press the graphite block tightly on the surface of the titanium alloy to form a diffusion couple. The pressure used is 100MPa.

[0045] Step 3: Connect the positive and negative electrodes at the upper and lower ends of the above diffusion couple and place them in a vacuum box. Under the action of the electric field, the interface atoms of titanium and graphite diffuse with each other. The current density is 50A / cm 2 , TiC wear-resistant layer was prepared, and the vacuum degree was 10 -3 , current frequency 40 Hz, pulse width 50 μs, processing time 1 min, and high-purity argon gas was injected during cooling.

[0046] Step 4: Put the titanium metal with high hardness carbide layer into a vacuum heat treatment furnace for low temperature annealing to make the structure of the carbide layer on the surface of the alloy more stable while maintaining the toughness and ductility of the core material. The low temperature annealing temperature is 550℃ and the holding time is 1.5h.

[0047] The high-hardness carburized layer on the titanium metal surface prepared in Example 3 has a carburized layer depth of 75 μm and an average microhardness of 1020.13 HV 0.02 The friction coefficient is 0.205 and the volume wear rate is 2.58ⅹ10 -6 mm 3 / Nm, with good wear resistance.

[0048] Example 4

[0049] Step 1: Select high-purity graphite with high electrical conductivity and high thermal conductivity as the carbon diffusion source, and the matrix titanium alloy is a high-strength titanium alloy. The carbon content of graphite is 99.995%, and the composition of the high-strength titanium alloy is 55% Ti and 45% Nb.

[0050] Step 2: Use alkaline cleaning agent to remove oil, wax and other organic substances from the surface of high-strength titanium alloy, clean it in an ultrasonic cleaning instrument for 5 minutes, dry it in a vacuum box, and then press the graphite block tightly on the surface of the titanium alloy to form a diffusion couple. The pressure used is 50MPa.

[0051] Step 3: Connect the positive and negative electrodes at the upper and lower ends of the diffusion couple and place them in a vacuum box. Under the action of the electric field, the interface atoms of titanium and graphite diffuse with each other. The current density is 75A / cm 2 , TiC wear-resistant layer was prepared, and the vacuum degree was 10 -2 , current frequency 50 Hz, pulse width 50 μs, processing time 5 min, and high-purity argon gas was injected during cooling.

[0052] Step 4: Put the titanium metal with high hardness carbide layer into a vacuum heat treatment furnace for low temperature annealing to make the structure of the carbide layer on the surface of the alloy more stable while maintaining the toughness and ductility of the core material. The low temperature annealing temperature is 550℃ and the holding time is 1.5h.

[0053] Figure 2 This is the microstructure of the high-hardness carbide layer prepared on the titanium metal surface in Example 4 of the present invention. It can be seen from the figure that the carbide layer is formed uniformly. The high-hardness carbide layer on the titanium metal surface prepared in Example 4 has a carburized layer depth of 85um and an average microhardness of 990.56HV on the alloy surface. 0.02 The friction coefficient is 0.215 and the volume wear rate is 3.27ⅹ10 -6 mm 3 / Nm, with good wear resistance.

[0054] Example 5

[0055] Step 1: Select high-purity graphite with high electrical conductivity and high thermal conductivity as the carbon diffusion source, and the matrix titanium alloy is a high-strength titanium alloy. The carbon content of graphite is 99.995%, and the composition of the high-strength titanium alloy is 55% Ti and 45% Nb.

[0056] Step 2: Use alkaline cleaning agent to remove oil, wax and other organic substances from the surface of high-strength titanium alloy, clean it in an ultrasonic cleaning instrument for 5 minutes, dry it in a vacuum box, and then press the graphite block tightly on the surface of the titanium alloy to form a diffusion couple. The pressure used is 50MPa.

[0057] Step 3: Connect the positive and negative electrodes at the upper and lower ends of the above diffusion couple and place them in a vacuum box. Under the action of the electric field, the interface atoms of titanium and graphite diffuse with each other. The current density is 100A / cm 2 , TiC wear-resistant layer was prepared, and the vacuum degree was 10 -3 , current frequency 50 Hz, pulse width 100 μs, processing time 20 s, and high-purity argon gas was injected during cooling.

[0058] Step 4: Put the titanium metal with high hardness carbide layer into a vacuum heat treatment furnace for low temperature annealing to make the structure of the carbide layer on the surface of the alloy more stable while maintaining the toughness and ductility of the core material. The low temperature annealing temperature is 550℃ and the holding time is 1.5h.

[0059] In Example 5, the titanium metal surface has a high hardness carburized layer, the carburized layer depth reaches 90um, and the average microhardness of the alloy surface is 899.32HV 0.02 The friction coefficient is 0.312 and the volume wear rate is 1.12 x 10 -5 mm 3 / Nm, with good wear resistance.

[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-hardness carburized layer on the surface of titanium metal, characterized in that: The specific steps include: Step 1, selecting high-purity graphite with high electrical conductivity and high thermal conductivity as a carbon diffusion source, and selecting a high-strength titanium alloy as the matrix titanium alloy; Step 2, placing the high-strength titanium alloy in an ultrasonic cleaning instrument, removing oil, wax and other organic substances on the surface of the high-strength titanium alloy by cleaning with an alkaline cleaning agent, then placing the high-strength titanium alloy in a vacuum box for drying, and finally pressing a graphite block tightly on the surface of the high-strength titanium alloy to form a diffusion couple, wherein the upper end of the diffusion couple is the graphite block and the lower end is the high-strength titanium alloy, wherein the entire outer surface of the high-strength titanium alloy is pressed with the graphite block; Step 3, the upper and lower ends of the diffusion couple formed in step 2 are connected to positive and negative electrodes respectively, and placed in a vacuum box, and the interface atoms of the high-strength titanium alloy and graphite diffuse with each other under the action of the electric field, so that a TiC wear-resistant layer is prepared on the surface of the high-strength titanium alloy; Step 4, placing the high-strength titanium alloy with a TiC wear-resistant layer on the surface prepared in step 3 into a vacuum heat treatment furnace for low-temperature annealing treatment, and finally preparing a high-hardness carbide layer on the surface of the high-strength titanium alloy.

2. The method for preparing a high-hardness carbide layer on the surface of titanium metal according to claim 1, characterized in that: In step 1, the carbon content of graphite is greater than 99.99%, and the high-strength titanium alloy composition is 55% Ti content and 45% Nb content.

3. The method for preparing a high-hardness carbide layer on the surface of titanium metal according to claim 1, characterized in that: In step 2, the high-strength titanium alloy is cleaned in an ultrasonic cleaning instrument for 5-10 minutes.

4. The method for preparing a high-hardness carbide layer on the surface of titanium metal according to claim 1, characterized in that: In step 2, the high-strength titanium alloy is placed in a vacuum oven and dried at a temperature of 160°C.

5. The method for preparing a high-hardness carbide layer on the surface of titanium metal according to claim 1, characterized in that: In step 2, the graphite block is tightly pressed against the surface of the high-strength titanium alloy at a pressure of 50-100 MPa.

6. The method for preparing a high-hardness carbide layer on the surface of titanium metal according to claim 1, characterized in that: In step 3, the vacuum degree of the vacuum box is 10 -2 -10 -3 , electric field conditions: current density 10-100A / cm 2 , current frequency 30-50Hz, pulse width 50-100μs, processing time 20s-5min, cool to room temperature after power-on, and inject high-purity argon into the vacuum box during cooling.

7. The method for preparing a high-hardness carbide layer on the surface of titanium metal according to claim 1, characterized in that: In step 4, the low-temperature annealing temperature is 550° C., and the low-temperature annealing time is 1.5 h.

8. A high-hardness carbide layer is prepared on the surface of titanium metal according to the method for preparing a high-hardness carbide layer on the surface of titanium metal according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • High-toughness, high-rigidity and pressure-proof coating on titanium alloy surface and preparation method thereof

    CN105695981A

  • Preparation method of surface titanium carbide metal product

    CN110257756A

  • Nickel-based alloy low-temperature ion carbonitriding method

    CN116377376A

  • Process for glow ion hydrogen-free carbonizing titanium surface

    CN1451779A

  • Baking treatment method for titanium alloy

    JP2002212694A

Cited By

  • Method for preparing high-hardness and high-wear-resistance CNx coating on titanium alloy surface

    CN120591860A